2001
DOI: 10.1103/physrevb.64.054201
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization under electropulsing suggesting a resonant collective motion of many atoms and modification of thermodynamic parameters in amorphous alloys

Abstract: For melt-spun amorphous (a-)Cu 50 Ti 50 and a-Pd 80 Si 20 , crystallization under electropulsing was studied by means of the discharge of a condenser with initial current density i d0 of the order of 10 9 A/m 2 and decay time in between 2 and 0.1 ms, where a specimen was sandwiched by AlN/BN substrates to minimize an effect of joule heating. The crystallization proceeds during electropulsing when i d0 is higher than the threshold i d0,c. Here i d0,c is a function of and shows a minimum value of 1.4ϫ10 9 A/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…The crystallization of the amorphous phase is induced not only by thermal annealing but other external factors such as electron irradiation, 14,15) focused ion beam (FIB), 16) electropulsing 17,18) and high pressure. 19) We found that electron irradiation can induce nanocrystallization of an amorphous phase in metallic glasses in which nanostructure cannot be easily realized by thermal annealing.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization of the amorphous phase is induced not only by thermal annealing but other external factors such as electron irradiation, 14,15) focused ion beam (FIB), 16) electropulsing 17,18) and high pressure. 19) We found that electron irradiation can induce nanocrystallization of an amorphous phase in metallic glasses in which nanostructure cannot be easily realized by thermal annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization of the glassy phase is induced not only by heat treatments but by other methods such as electron irradiation, [9][10][11] ion irradiation, 12) electropulsing 13) and high pressure. 14) It has been demonstrated that electron irradiation can induce nanocrystallization in metallic glasses in which nanoscale structures cannot easily be realized by heat treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Mizubayashi et al [18][19][20][21][22][23][24] have investigated effects of passing electric current on the structural relaxation and crystallization of some kinds of amorphous alloys, which shows that crystallization is very much accelerated by the electropulsing far below the normal crystallization temperature without the pulsing. Recently, elastic and anelastic properties of Zr 55 Al 10 Ni 5 Cu 30 25) and Pd 40 Ni 40 P 20 26) bulk metallic glasses around T g have been studied with the electromagnetic acoustic resonance (EMAR) method within the frequency range of 300-1500 kHz.…”
Section: Introductionmentioning
confidence: 99%